2015
DOI: 10.1002/2014jg002788
|View full text |Cite
|
Sign up to set email alerts
|

Importance of nondiffusive transport for soil CO2 efflux in a temperate mountain grassland

Abstract: Soil respiration and its biotic and abiotic drivers have been an important research topic in recent years. While the bulk of these efforts has focused on the emission of CO2 from soils, the production and subsequent transport of CO2 from soil to atmosphere received far less attention. However, to understand processes underlying emissions of CO2 from terrestrial ecosystems, both processes need to be fully evaluated. In this study, we tested to what extent the transport of CO2 in a grassland site in the Austrian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 65 publications
2
59
2
1
Order By: Relevance
“…Variability was also unrelated to sunlight, humidity, soil temperature, soil moisture, soil efflux, and CO 2 mole fraction increase during chamber closure. This contrasts with other studies that have shown correlations between soil CO 2 and/or soil efflux with these environmental forcing mechanisms (e.g., Davidson et al, 1998;Roland et al, 2015;Sánchez-Cañete et al, 2013;Savage et al, 2013;Subke et al, 2003), highlighting the variability in these processes across the landscape.…”
Section: R Bowling Et Al: Environmental Forcing Does Not Induce contrasting
confidence: 99%
See 4 more Smart Citations
“…Variability was also unrelated to sunlight, humidity, soil temperature, soil moisture, soil efflux, and CO 2 mole fraction increase during chamber closure. This contrasts with other studies that have shown correlations between soil CO 2 and/or soil efflux with these environmental forcing mechanisms (e.g., Davidson et al, 1998;Roland et al, 2015;Sánchez-Cañete et al, 2013;Savage et al, 2013;Subke et al, 2003), highlighting the variability in these processes across the landscape.…”
Section: R Bowling Et Al: Environmental Forcing Does Not Induce contrasting
confidence: 99%
“…4 to dramatic changes in Fig. 3 of Sánchez-Cañete et al, 2013), and soil CO 2 was not correlated with wind speed, friction velocity, or pressure. Large changes in soil CO 2 were related to rain events (Fig.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations